Marketing Management System of Dropshipping Islamic Economic Perspective (Case Study at Purwokerto Online We Skincare Store) - Nurlaila, Alfa Rizka (International Conference of Moslem Society, 2019)
Competitive market competition requires an entrepreneur to prepare a strategy and regulate the right and mature marketing management. Marketing is one of the activities carried out by the company to maintain the continuity of its business. The marketing process begins before goods are produced, and does not end with sales. Online Shop is a shop that applies marketing management with a dropshipping system. Which system is considered beneficial for business people who do not have the capital and the dropshipper does not need to buy goods first. In this study, researcher choosed the online shop â€œWe Skincareâ€ Purwokerto as the research subject. This research is field research, with the type of research is qualitative research. The technique of collecting data used observation, documentation, and interview. In this case, the researcher describe one problem which is then analyzed based on the perspective of Islamic economics, namely by: describing the marketing management of online shop â€œWe Skincareâ€ Purwokerto. Based on the research, marketing management applied in online shop â€œWe Skincareâ€ Purwokerto is 4P marketing strategy. In this case, the online shop â€œWe Skincareâ€ Purwokerto explained the characteristics of products, packaging, and services provided or affordability, which means affordable prices but with good quality and results. Online shop â€œWe Skincareâ€ Purwokerto used direct distribution channel as the main strategy for attracting consumers. And the promotion is carried out through social media.